Human genes and genomes : science health society - Rosenberg, Leon E. (Elsevier Academic Press, 2012)
In the nearly 60 years since Watson and Crick proposed the double helical structure of DNA, the molecule of heredity, waves of discoveries have made genetics the most thrilling field in the sciences. The study of genes and genomics today explores all aspects of the life with relevance in the lab, in the doctor's office, in the courtroom and even in social relationships. In this helpful guidebook, one of the most respected and accomplished human geneticists of our time communicates the importance of genes and genomics studies in all aspects of life. With the use of core concepts and the integration of extensive references, this book provides students and professionals alike with the most in-depth view of the current state of the science and its relevance across disciplines.